THE CONCEPT OF LOVE IN S.N. BULGAKOV’S PHILOSOPHICAL AND THEOLOGICAL CREATIVITY - Миргородский, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article concept of love in Sergey Bulgakov’s philosophical and theological creativity are investigated.